Critical success factors of micro entrepreneurs under the AIM and asnaf’s economic development programme / Farah Aida Ahmad Nadzri - Ahmad Nadzri, Farah Aida (Institute of Graduate Studies, UiTM, 2017)
The microfinance concept was introduced by Professor Muhammad Yunus in 1970s with the aspiration to improve the poor people live by providing them the accessibility to the financial services. Generally, the microfinance programs in Malaysia can be divided into two categories, repayable and non-repayable micro funds. As previous studies on repayable financing by Microfinance Institutions such as Amanah Ikhtiar Malaysia (AIM) suggested that in general, the programme has a positive socio-economic impact, empirical studies on the economic development programmes by Zakat Institutions that provide the non-repayable micro funds showed that the successful or effectiveness of this programme is questionable. Therefore, this thesis aims to study on the critical success factors of micro entrepreneurs under the AIM and Program Pembangunan Usahawan Asnaf Zakat Selangor (PPUAZ). Based on the previous literature, a conceptual framework is developed that the performance of micro entrepreneurs under the AIM and PPUAZ is causally related to four factors, namely financial management; human capital; social networking; and entrepreneurs’ characteristics. In order to meet the objective of this study, the quantitative (surveys) and qualitative (interviews) approaches are used. The surveys were conducted first in order to explain the relationship between the four critical success factors and the performance of the microentrepreneurs…